The Role of Corporate Governance in Influencing the Relationship Between Intellectual Capital and Financial Performance in the VUCA Era - Ririh Dian Pratiwi; Anis Chariri (Universitas Sebelas Maret, 2021)
This paper examines the ability of corporate governance in moderating the relationship between intellectual capital and financial performance. Resource Based Theory explains how companies use their resources to achieve financial performance, depending on their management. Intellectual capital is measured by the Value Added Intellectual Capital (VAIC) model, which consists of three components (VACA, VAHU, STVA). Financial performance in this paper is measured using Return on Assets (ROA). Corporate governance in this paper includes independent board of commissioners, managerial ownership and institutional ownership. This paper uses secondary data in the form of annual reports of manufacturing companies listed on the Indonesia Stock Exchange. The sample obtained by purposive sampling method amounted to 141. Data analysis was carried out by Moderating Regression Analysis (MRA), previously, the classical assumption test was carried out. The results showed that managerial ownership and institutional ownership were able to moderate the relationship between intellectual capital and financial performance. Meanwhile, the independent board of commissioners is unable to moderate the relationship berween intellectual capital and financial performance. The conclusion is that the amount of share ownership by managerial or institutional is able to control the company's intellectual capital in creating good financial performance. However, the proportion of independent commissioners is not able to influence the relationship between intellectual capital and financial performance. This research is able to contribute to the knowledge that intellectual capital is able to influence the achievement of the company's financial performance, which is influenced by the size of managerial ownership and institutional ownership. The VUCA era which is characterized by volatility, uncertainty, complexity and ambiguity certainly has an impact on the survival of an entity. Entities or companies with good governance will be able to manage their resources well (including intellectual capital) in producing optimal financial performance. Further research is suggested to add control variables such as firm size, or conduct research with the period before, during or after the crisis in a country.